This preview shows page 1. Sign up to view the full content.
Unformatted text preview: a b where a and b have no common factors. Then we have 3 = a 2 b 2 or 3 b 2 = a 2 . Thus 3  a 2 and by the above lemma 3  a . Let a = 3 k for some k Z . Thus 3 b 2 = (3 k ) 2 = 9 k 2 and dividing by 3 we get b 2 = 3 k 2 . Note that 3  b 2 and by the above lemma 3  b . Thus b = 3 l for some l Z . In conclusion a = 3 k and b = 3 l and thus a and b have the common factor 3. This contradicts what we assumed at the beginning and completes the proof. 1...
View
Full
Document
 Spring '09
 dd
 Math

Click to edit the document details